Morphological Diversity and Production of Six Sago (Metroxylon spp.) Accessions from Tana Luwu, South Sulawesi, Indonesia - Masluki, Masluki; Bintoro, Mochamad Hasjim; Agusta, Herdhata; Sudarsono, Sudarsono (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2024)
Tana Luwu area owns a relatively high diversity and production potential of sago, but it has not yet been managed optimally. This study aims to identify and analyze the diversity of morphological characteristics and the production of various sago accessions in Tana Luwu. Based on morphological characteristics, the sago palm in Tana Luwu is divided into two groups by the presence of thorns on the rachis and petioles. The presence of thorns has the largest coordinate axis angles, representing a higher diversity distance than other morphological characteristics. Some accessions show very high production potential, with a total production of 476.66 kg per dry tree starch. The average sago production in the six accessions is 276.40 kg per dry tree starch. Accessions with a yield potential > 200 kg per dry starch are observed in Kapa, Uso, Kasimpo, and Sabbe. Therefore, sago in these accessions is potentially developed to obtain superior varieties. Two significant morphological characteristics that contribute to sago production are stem height (r = 0.73) and the number of leaves (r = 0.78).